2014
DOI: 10.5194/acp-14-13281-2014
|View full text |Cite
|
Sign up to set email alerts
|

A joint data assimilation system (Tan-Tracker) to simultaneously estimate surface CO<sub>2</sub> fluxes and 3-D atmospheric CO<sub>2</sub> concentrations from observations

Abstract: Abstract.We have developed a novel framework ("TanTracker") for assimilating observations of atmospheric CO 2 concentrations, based on the POD-based (proper orthogonal decomposition) ensemble four-dimensional variational data assimilation method (PODEn4DVar). The high flexibility and the high computational efficiency of the PODEn4DVar approach allow us to include both the atmospheric CO 2 concentrations and the surface CO 2 fluxes as part of the large state vector to be simultaneously estimated from assimilati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…Recently, Tian et al (2014) developed a new surface CO 2 flux data assimilation system, Tan-Tracker, by incorporating a joint PODEn4DVar assimilation framework into the GEOS-Chem model on the basis of Peters et al (2005Peters et al ( , 2007 and Kang et al (2011Kang et al ( , 2012. They discussed in detail that the assimilation of CO 2 surface fluxes could be improved through the use of simultaneous assimilation of CO 2 concentrations and CO 2 surface fluxes.…”
Section: Z Peng Et Al: a Regional Carbon Data Assimilation Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Tian et al (2014) developed a new surface CO 2 flux data assimilation system, Tan-Tracker, by incorporating a joint PODEn4DVar assimilation framework into the GEOS-Chem model on the basis of Peters et al (2005Peters et al ( , 2007 and Kang et al (2011Kang et al ( , 2012. They discussed in detail that the assimilation of CO 2 surface fluxes could be improved through the use of simultaneous assimilation of CO 2 concentrations and CO 2 surface fluxes.…”
Section: Z Peng Et Al: a Regional Carbon Data Assimilation Systemmentioning
confidence: 99%
“…Miyazaki, 2009;Liu et al, 2011Liu et al, , 2012Feng et al, 2011;Tangborn et al, 2013;Huang et al, 2014). In addition, previous studies showed that the simultaneous assimilation of CO 2 concentrations and surface CO 2 fluxes can largely eliminate the uncertainty in initial CO 2 concentrations on the CO 2 evolution Tian et al, 2014). Therefore, we also use the simultaneous assimilation framework; the ensemble Kalman filter (EnKF) was used to constrain CO 2 concentrations and the ensemble Kalman smoother (EnKS) was used to optimize surface CO 2 fluxes.…”
Section: Z Peng Et Al: a Regional Carbon Data Assimilation Systemmentioning
confidence: 99%
See 3 more Smart Citations